Financial Investment Pattern and Preference of College Professors at Trichy City - Dr. G. Balamurugan; V Sivanesan (International Journal of Engineering and Management Research, 2022)
Financial Investments are the commitments that are made by individuals with any financial and non-financial instruments for gaining a better and profitable return in future for a particular objective. The financial and non-financial investment instruments act as a medium or a driving tool for investment decisions of individuals. From the available investment avenues one must select the appropriate one that he feels safer or good to invest. The person who is going to make investments should be aware of all knowledge about investments and should be aware of how it is going to fulfil his objective. The person who is investing should be known of all the investment avenues available for making investments. Such avenues are employee provident fund, public provident fund, mutual funds, insurance, bank deposits, real estate, gold, stock market. This study is about to analyse the investment pattern of college professors and their attitude towards investment avenues. It also aims to identify the reason behind making investment and to find their objective for making investment. It helps to find the behaviour of individuals while making investments. Further this study helps to find the relationship of various demographic factors of the respondents and factors associated while making investment decisions. Such factors include time period of their investment, investment avenues, risk factors, returns etc.